2016
DOI: 10.1002/art.39664
|View full text |Cite
|
Sign up to set email alerts
|

Role of Anti–Carbamylated Protein Antibodies Compared to Anti–Citrullinated Protein Antibodies in Indigenous North Americans With Rheumatoid Arthritis, Their First‐Degree Relatives, and Healthy Controls

Abstract: Objective. Rheumatoid arthritis (RA) is characterized by the presence of autoantibodies, including seropositivity for rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPAs). In addition, antibodies to carbamylated proteins (anti-CarP) are present in patients with RA and are associated with joint damage. This study was undertaken to assess the presence of anti-CarP antibodies in indigenous North Americans (First Nations [FN] populations) with RA compared to their at-risk first-degree relatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 34 publications
1
35
0
1
Order By: Relevance
“…While a positive anti-CCP test in RA is typically citrulline-dependent [7], it has been suggested that anti-CCP in other conditions is generally not, and thus, also reacts with the corresponding cyclic arginine peptide (anti-CAP) [8, 9]. During the last years, it has been repeatedly shown that antibodies targeting carbamylated proteins (anti-CarP) may occur in anti-CCP/rheumatoid factor (RF) negative cases [1012]. Like RF and anti-CCP, anti-CarP antibodies can also be detected many years before the onset of RA [1315].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a positive anti-CCP test in RA is typically citrulline-dependent [7], it has been suggested that anti-CCP in other conditions is generally not, and thus, also reacts with the corresponding cyclic arginine peptide (anti-CAP) [8, 9]. During the last years, it has been repeatedly shown that antibodies targeting carbamylated proteins (anti-CarP) may occur in anti-CCP/rheumatoid factor (RF) negative cases [1012]. Like RF and anti-CCP, anti-CarP antibodies can also be detected many years before the onset of RA [1315].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation, smoking and renal failure have been reported to increase the non-enzymatic post-translational modification in which cyanate binds to molecules containing primary amine or thiol groups and forms carbamyl groups [16]. Carbamylation of proteins can lead to the loss of tolerance with formation of antibodies directed against carbamylated proteins (anti-CarP antibodies) in susceptible individuals [1012]. …”
Section: Introductionmentioning
confidence: 99%
“…The value of determining various autoantibodies appears to be remarkably different depending on what phase of the disease is studied. In at‐risk individuals without arthralgia, triple positivity for autoantibodies (RF, ACPA, and anti‐CarP) has a higher association with disease development . Moreover, in a meta‐analysis investigating various cohorts of presymptomatic individuals, triple positivity resulted in high specificity (98%‐100%), but low sensitivity (11%‐39%) for prediction of RA development .…”
Section: Clinical Relevance Of Autoantibodies In Ramentioning
confidence: 96%
“…In at-risk individuals without arthralgia, triple positivity for autoantibodies (RF, ACPA, and anti-CarP) has a higher association with disease development. 83 Moreover, in a meta-analysis investigating various cohorts of presymptomatic individuals, triple positivity resulted in high specificity (98%-100%), but low sensitivity (11%-39%) for prediction of RA development. 84 However, in individuals who have already progressed to the stage of arthralgia, anti-CarP did not have an additive value to ACPA and RF in predicting arthritis onset.…”
Section: Clini C Al Rele Van Ce Of Autoantibod Ie S In R Amentioning
confidence: 99%
“…Other described predictive markers like the acute-phase reactants erythrocyte sedimentation rate and C reactive protein and additional markers can be incorporated in the development of prediction models. Indeed, recent insight into the specificity of the combined presence of ACPA, rheumatoid factor and anticarbamylated protein antibodies provides interesting possibilities in further narrowing down persons at risk 7 8…”
mentioning
confidence: 99%